Mechanical and Durability Properties of Concrete with Ground Waste Glass Sand - Oliveira, Luiz António Pereira de (2010)
This paper examines the possibility of using finely ground waste glass as partial natural sand replacement in concrete. The reduction of waste glass particle size was accomplished in the laboratory by crushing and grinding the waste glass in a jar mill. The compressive strength at 7, 28 and 90 days, was determined for different ground waste glass sand percentage replacement in concrete. Absorption and permeability tests were also carried out. A test method was followed to verify the potential concrete expansion caused by the alkali silica reaction. The results showed a very significant compressive strength improvement with the increasing of percentage replacement of natural sand by ground waste glass. A higher compressive strength was obtained with a lower expansion verified by the bar tests. The same trend for durability properties were also observed in this study. The results obtained attested the high possibility of recycling and using of the ground waste glass collected in central region of Portugal as natural sand replacement in concrete mixtures.